2016
DOI: 10.1021/acs.langmuir.6b00012
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Methods for Covalent Attachment of Ethynylferrocenes to Electrode Surfaces: Comparison of Ethynyl Activation Processes

Abstract: The electrochemical oxidation of ferrocenes having an H- or Li-terminated ethynyl group has been studied, especially as it relates to their covalent anchoring to carbon surfaces. The anodic oxidation of lithioethynylferrocene (1-Li) results in rapid loss of Li(+) and formation of the ethynyl-based radical FeCp(η(5)-C5H4)(C≡C), (1, Cp = η(5)-C5H5), which reacts with the electrode. Chemically modified electrodes (CMEs) were thereby produced containing strongly bonded, ethynyl-linked monolayers and electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 67 publications
(107 reference statements)
1
38
0
Order By: Relevance
“…The anodic deposition processes of compounds 1 , 4 , and 5 have already been partially described . The present paper offers additional examples of ethynyl‐attached ferrocene derivatives and provides new information on how the electrolyte medium may affect both the surface deposition process and the voltammetry of the surface‐bound species.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The anodic deposition processes of compounds 1 , 4 , and 5 have already been partially described . The present paper offers additional examples of ethynyl‐attached ferrocene derivatives and provides new information on how the electrolyte medium may affect both the surface deposition process and the voltammetry of the surface‐bound species.…”
Section: Resultsmentioning
confidence: 79%
“…Recently it has been shown that radical‐based electrografting processes are effective in preparing chemically modified electrodes to which molecules are covalently attached through an ethynyl group . We have previously described an assortment of methods whereby metallocenes derivatized at a cyclopentadienyl ring with a terminal ethynyl group can be covalently attached to carbon surfaces .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The covalent modification of carbon surfaces by electrografting began in the last decade of the past century with the oxidation of primary amines and the reduction of aryldiazonium cations, which allowed the attachment of organic moieties on carbon surfaces through N−C and C−C bonds respectively . After these pioneering studies, a wide variety of alternative electrografting methods have been developed, which involve the generation of free radicals at the electrode‐solution interface, either in reduction or oxidation processes . An advantage of these covalently modified surfaces is the fact that they have high chemical and physical stability and show similar properties to the attached molecules.…”
Section: Introductionmentioning
confidence: 99%